2022
DOI: 10.2903/sp.efsa.2022.e200506
|View full text |Cite
|
Sign up to set email alerts
|

Theme (Concept) paper ‐ Application of OMICS and BIOINFORMATICS Approaches: Towards Next Generation Risk Assessment

Abstract: OMICS and BIOINFORMATICS Approaches for Next Generation Risk Assessmentwww.efsa.europa.eu/publications 2 EFSA Supporting publication 2022.e200506Acknowledgements: EFSA wishes to thank the following for drafting the scientific output: Also, Jaime

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, the comprehensive molecular characterisation and risk assessment should also comprise “Omics” (such as transcriptomics, proteomics and metabolomics) as discussed by EFSA ( EFSA et al, 2022c ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the comprehensive molecular characterisation and risk assessment should also comprise “Omics” (such as transcriptomics, proteomics and metabolomics) as discussed by EFSA ( EFSA et al, 2022c ).…”
Section: Discussionmentioning
confidence: 99%
“…As DNA sequencing will not always allow the identification of the associated unintended biological effects, additional methods, such as transcriptomics and metabolomics, should be used to draw reliable conclusions [see ( Kawall et al, 2020 ; EFSA et al, 2022c )]. If no unintended genetic alterations are detected that are specific to NGT processes, risk assessment may focus on the intended changes.…”
Section: Consequences For a Comprehensive Molecular Characterisation ...mentioning
confidence: 99%
“…Here, it was suggested that to preserve the biological, genetic, and cultural services that the microbiome provides, microbial communities should be protected via the assessment of the impacts of PPPs on “diversity.” Diversity, in this case, is defined in the scientific opinion document as either phylogenetic or functional, introducing the potential for including microbial community composition within a PPP risk assessment context. This suggestion was further supported in a recent EFSA conceptual paper in which the intention to explore incorporation of the impacts of chemicals on soil bacterial communities was explicitly stated (European Food Safety Authority et al, 2022). This, therefore, indicates the possibility that changes in microbial community composition and diversity may become an endpoint in a future European PPP risk assessment.…”
Section: Introductionmentioning
confidence: 87%
“…One of the major hurdles is the transferability of results from, for example, in vitro cell assays to a whole organism [ 98 ]. To overcome these problems, stepwise approaches in adverse outcome pathways (AOP) are used to build a risk assessment from a variety of independent results [ 4 , 47 ]. The OECD, among others, is enabling globally harmonised principles and supports the development of the NGRA, also for microbial pesticides [ 16 , 77 ].…”
Section: Introductionmentioning
confidence: 99%